Usefulness of ultrasonography guided femoral and lateral femoral cutaneous nerve blocks in providing analgesia before giving spinal anaesthesia in patients undergoing surgery for intertrochanteric fracture of femur: A randomized clinical trial - Vishwanath Meti; K Lohit; G Amarappa; T C Balaraju; S Lavanya (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: It is challenging to give the patient position for subarachnoid block (SAB) as intertrochanteric (IT) fracture of the femur produces intolerable pain. In this study, we have analyzed the usefulness of combined ultrasonography (USG)-guided femoral nerve block (FNB) and lateral femoral cutaneous nerve block (LFCNB) to reduce the fracture pain before performing SAB. Material and Methods: A prospective, randomized, comparative study was conducted on 60 American society of anesthesiologists (ASA) grade I and II patients (18-80 years) scheduled for elective IT fracture surgery. Group A (n = 30) patients received USG-guided FNB and LFCNB using 0.75% ropivacaine before SAB. Group B patients (n = 30) received SAB only. All the patients received SAB (3 mL of 0.5% bupivacaine) by an anesthesiologist blinded to the patient groups. The patients were observed for quality of patient positioning for SAB, perioperative visual analog scale (VAS) scores, time to administration of SAB, and duration of analgesia and motor blockade. Statistical analysis was done by Student's t-test and Chi-square test. Results: Baseline VAS score (T1) was similar in both the groups. Mean T2 (VAS score just before SAB) in group-A (3.2 ± 0.98) was lower compared to group-B (8.23 ± 0.7) with P < 0.0001.The quality of patient positioning in group-A was good to optimal but in group-B, it was satisfactory to not satisfactory. Group-A had longer mean duration of analgesia 804 ± 114.28 minutes with P value < 0.0001 than group-B in which it was 200 ± 28.77 min. Backache was significant in group-B with P value of 0.038 compared to group-A. Conclusion: USG-guided FNB and LFCNB can be used as an effective supplementation to SAB in patients undergoing surgery for IT fracture of the femur as it reduces fracture site pain, provides good patient positioning during SAB, and prolongs postoperative analgesia.